PENGAWETAN GEDEBOG SEBAGAI PERANGKAT PERTUNJUKAN WAYANG KULIT PURWA DENGAN REKAYASA PENGURANGAN KADAR AIR - Sapto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This article discusses the preservation of banana trunks or banana tree trunks as a performance art device for wayang kulit purwa. This preservation is important considering that the trunk is the puppet performance device that cannot last long. In fact, its existence is very vital, especially as a medium for attaching puppets during the performance. The preservation method is carried out experimentally by reducing the water content of the trunk. As a result, the trunk, which usually only lasts one to two days, can be preserved for approximately one week. This preservation engineering of the trunk is very useful, especially in learning the art of wayang kulit purwa, both in formal and non-formal education.